Perancangan Sistem Kendali untuk Pergerakan Lengan Robot 4-DOF - Pawelloi, A. Irmayani; Basri, Muh; Irwandi, Irwandi (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2024)
Robotic arms are one of the rapidly developing technologies in the field of robotics, with the need for efficient and reliable control systems. This research designed a robotic arm control system based on the ESP32 microcontroller with Bluetooth connectivity, using seven push buttons to control servo movements on four main components: shoulder, arm, gripper, and base. The purpose of the study is to analyze the performance of servo motion and the effectiveness of Bluetooth communication in controlling robot movement. The research method includes testing the response of servo movement at a certain angle range and evaluating Bluetooth communication capabilities at various distances and conditions. The results show that the servo motor has stable performance with minimal variation in movement time, with the average movement time varying between 1.64-6.82 seconds depending on the component. Bluetooth communication tests revealed 100% reliability at distances up to 15 meters without barriers, but decreased significantly to 40% at distances of 20 meters and only 10% at distances of 15 meters with barriers. The system features a 20x4 LCD for real-time monitoring and supports multiple control modes. This research contributes to the development of a robotic arm control system that is responsive and has potential applications in various industrial fields, with advanced recommendations to optimize Bluetooth communication range and quality.